2021
DOI: 10.1101/2021.05.01.442219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning-Inferred Multiplex ImmunoFluorescence for IHC Image Quantification

Abstract: Reporting biomarkers assessed by routine immunohistochemical (IHC) staining of tissue is broadly used in diagnostic pathology laboratories for patient care. To date, clinical reporting is predominantly qualitative or semi-quantitative. By creating a multitask deep learning framework referred to as DeepLIIF, we are presenting a single step solution to nuclear segmentation and quantitative single-cell IHC scoring. Leveraging a unique de novo dataset of co-registered IHC and multiplex immunoflourescence (mpIF) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We expect that computational advances will also facilitate the identification and dissection of complex multicellular modules that can serve as the basis for new diagnostics and therapeutics. Machine learning is used to segment out individual cells in images for single cell quantification [26] and to quantify lower-plex immunohistochemistry data [27]. Machine learning approaches could be extended to enable segmentation of complex, multicellular structures, such as the glomeruli of the kidney, and to automate cell type annotation.…”
Section: Trends In Cancermentioning
confidence: 99%
“…We expect that computational advances will also facilitate the identification and dissection of complex multicellular modules that can serve as the basis for new diagnostics and therapeutics. Machine learning is used to segment out individual cells in images for single cell quantification [26] and to quantify lower-plex immunohistochemistry data [27]. Machine learning approaches could be extended to enable segmentation of complex, multicellular structures, such as the glomeruli of the kidney, and to automate cell type annotation.…”
Section: Trends In Cancermentioning
confidence: 99%
“…More recently, although alternative approaches are actively pursued [51][52][53][54], well consolidated methodologies derived by CNNs are still being used [55]. In particular, two families of algorithms deserve a mention for the rather large popularity gained in the last few years, both stemming from the original R-CNN model [56].…”
Section: Lymphocyte Detection and Density Mapsmentioning
confidence: 99%
“…There are several open source tools for segmenting cells in pathology slides stained with H&E (Hematoxylin & Eosin), IHC (Hematoxylin + brown DAB substrate), and multiplex [5]. These tools are available as (1) web apps (easiest to run with no prerequisite computational expertise), (2) plugins for image analysis toolboxes (mandates familiarity with these toolboxes), (3) coding notebooks (requires basic coding skills), and (4) code-based pipelines (requires significant coding expertise). In this demonstration paper, we focus on tools that are available as web apps and hence are accessible to a broad audience, including both image analysis experts and non-experts.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case with the research multiplex immunofluorescence platforms, for example, that output each marker as an independent channel that can be visualized and analyzed separately or as composites. Leveraging this insight, we developed DeepLIIF (published in Nature Machine Intelligence [1]) for virtual multiplex immunofluorescence restaining of standard IHC slides that performs stain deconvolution and cell segmentation/classification in a single step to output clinically relevant IHC scores (mostly quantified as relevant DAB brown cells divided by the total cells). We showed that DeepLIIF, trained on co-registered IHC and multiplex immunofluorescence images, not only achieves state-of-the-art results in IHC nuclear protein marker scoring (Ki67, ER, PR, P53) but also works out-of-the-box for H&E nuclei segmentation as well as cytoplasmic markers (that are expressed close to the nuclei, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation